The Ion/Electron Temperature Characteristics of Polar Cap Classical and Hot Patches and Their Influence on Ion Upflow. Issue 16 (28th August 2018) - Ma, Yu‐Zhang; Zhang, Qing‐He; Xing, Zan‐Yang; Heelis, Roderick A.; Oksavik, Kjellmar; Wang, Yong
Abstract: The term of "polar cap hot patch" is a newly identified high‐density plasma irregularity at high latitudes, which is associated with high electron temperature and particle precipitation, while a classical polar cap patch has lower electron temperature. To investigate characteristics of hot patches versus classical patches, five years of in situ database of plasma observations from the DMSP satellites was analyzed. For the first time, we show how the ion/electron temperature ratio (or temperature difference) can be used to distinguish between classical and hot patches. For classical patches ( T i / T e  > 0.8 or T e  <  T i  + 600 K), the vertical ion flux is generally downward. For hot patches ( T i / T e  < 0.8 or T e  >  T i  + 600 K), the vertical ion flux is generally upward. The highest upflow occurrence was found near the polar cap boundary, associated with hot patches, particle precipitation, strong convection speed, and localized field‐aligned currents. This result shows that the polar cap hot patches may play a very important role in solar wind‐magnetosphere‐ionosphere coupling processes. Plain Language Summary: The polar ionosphere is one of the most dynamical regions on Earth, where energy, mass, and momentum can flow between the solar wind and the upper atmosphere. One important phenomenon in the polar ionosphere is polar cap patches, which are islands of high‐density plasma. The polar cap patches are often associated with sharp density gradients that cause disturbances to radio signals, satellite navigation, and communication. A new type of patch, associated with strong scintillation, has recently been identified in literature and called "polar cap hot patch." In this paper we compare the plasma characteristics of "classical" and "hot" patches. For the first time, we show how the ion/electron temperature ratio (or temperature difference) can be used to distinguish between classical and hot patches. We find high ion upflow occurrence associated with particle precipitation in the hot patches. The ion upflow flux increases with increased field‐aligned current and convection speed. This shows that the polar cap hot patches may play a very important role in solar wind‐magnetosphere‐ionosphere coupling processes. Key Points: We find high ion upflow occurrence near MLAT ~78° and associated with particle precipitation (high T e, low T i / T e, high FAC) The ion upflow flux increases with increased FAC and convection speed. When T i / T e ratio increases, the upflow occurrence and flux decreases The average vertical flow turns upward when T i / T e  < 0.8 or T e  >  T i  + 600 K